Preparation method and application of adsorbent for water treatment
By crosslinking the arynamis shell with nano Fe3O4 particles to prepare it into a magnetic iron oxide arynamis shell, the problem of low copper ion removal efficiency in wastewater is solved, and fast and efficient copper ion adsorption and easy recovery of adsorbents are achieved.
Patent Information
- Application Number
- CN202411723232.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to effectively remove copper ions in wastewater, and the adsorption performance of traditional biological materials to copper is limited and difficult to recover.
Made into magnetic iron oxide cyst shell (LC-FeO) by crosslinking the cyst shell with nanoFe3O4 particles. It is used as an adsorbent for water treatment. Its internal pore structure makes the nanoFe3O4 particles grow in a limited domain, improving adsorption performance .
The rapid and efficient removal of copper ions in water is achieved, and due to the magnetic properties of nanoparticles, the adsorbent is easy to recover, reducing the treatment cost.
Smart Images

Figure CN119386818A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of water treatment, and in particular to a preparation method and application of an adsorbent for water treatment. Background Art
[0002] Copper is an essential trace element for plants, animals and humans in the environment, and is particularly critical for plant growth. Copper deficiency can lead to impaired biological functions, while excessive copper can damage cell membranes and cause plant root rot, thereby reducing vegetation cover and growth, and having an adverse impact on the ecosystem. The main sources of copper pollution include mining activities and the uncontrolled use of copper-containing pesticides, such as copper hydroxide and copper sulfate.
[0003] In order to control copper pollution, a variety of treatment technologies have been developed, including chemical precipitation, ion exchange, membrane filtration, coagulation-flocculation, flotation, electrochemical methods and adsorption. Among them, the adsorption method has been widely studied because of its economic efficiency. Many biomaterials, such as wheat, corn straw, sawdust, etc., are rich in functional groups such as carboxyl, amide, and hydroxyl groups, and have a high affinity for copper ions, and are used as copper ion adsorbents in wastewater. However, these materials have limited adsorption properties for copper and are difficult to recycle, which greatly increases the treatment cost. Studies have found that nanoparticles have a high adsorption capacity for copper ions, but because nanoparticles have poor dispersibility in water and are very easy to agglomerate, the specific surface area is reduced, and the adsorption capacity is also greatly affected. To solve this problem, attempts have been made to load nanoparticles onto biochar, but the mesoporous and microporous structures of many biochars limit the uniform growth of nanoparticles and affect the adsorption effect.
[0004] Therefore, it is of great significance to develop a stable, efficient, economical and recyclable adsorbent as a new process for removing copper ions from wastewater and solving copper pollution in wastewater. Summary of the invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a preparation method and application of an adsorbent for water treatment, which can achieve rapid and efficient removal of copper ions in water.
[0006] The present invention provides a method for preparing an adsorbent for water treatment, comprising the following steps:
[0007] a) ultrasonically washing the Artemia cysts that have been washed by stirring a mixture of water and ethanol and drying the mixture to obtain a clean material;
[0008] b) firing the obtained materials at different pyrolysis temperatures to obtain Artemia cysts with different pore sizes;
[0009] c) stirring the obtained Artemia cysts and the prepared nano Fe3O4 particles and calcining them at a high temperature to obtain an adsorbent for water treatment.
[0010] Preferably, in step a), the concentration of the water and ethanol mixture is a water to ethanol mass ratio of 1 to 3, and the stirring time is 3 to 6 hours;
[0011] Ultrasound time is 20 to 40 minutes;
[0012] The drying temperature is 50-80°C and the time is 6-9 hours;
[0013] Preferably, in step b), the pyrolysis temperature is 0 to 900°C;
[0014] The firing time is 4 to 7 hours;
[0015] Preferably, in step c), the nano Fe3O4 particles are prepared by stirring and mixing FeCl2·4H2O and FeCl3·6H2O in a mass ratio of 1 to 5;
[0016] Add 10-30 mL of aqueous ammonia (volume ratio is 10-40%) and heat at 60-90° C. for 10-40 minutes;
[0017] Firing at 50-300°C for 1-4 hours;
[0018] The mass ratio of Artemia cyst shell to nano-Fe3O4 is 1 to 5, and the mixture is stirred for 1 to 3 hours;
[0019] Drying at 60-100°C for 8-16 hours and firing at 200-700°C for 1-4 hours;
[0020] The present invention also provides an adsorbent for water treatment prepared by the method for preparing the adsorbent for water treatment described above.
[0021] The present invention also provides a water treatment method, comprising the following steps:
[0022] A) dissolving cupric sulfate pentahydrate into distilled water to obtain a copper ion solution;
[0023] B) adding a water treatment adsorbent to the copper ion solution to perform an adsorption reaction;
[0024] The water treatment adsorbent is the water treatment adsorbent provided in the above embodiment;
[0025] C) performing solid-liquid separation on the water obtained in step B) to obtain treated water.
[0026] Preferably, in step A), before dissolving copper sulfate pentahydrate into distilled water, the step further comprises: using 0.1 to 0.6 g of copper sulfate pentahydrate;
[0027] The amount of distilled water used is 50-200 mL;
[0028] In step B), the amount of adsorbent for water treatment is 0.01 to 1 g / L;
[0029] The water treatment adsorbent stays in the water body for 0.5 to 4 hours;
[0030] The adsorption reaction is carried out at room temperature;
[0031] In step C), the pore size of the filter used for solid-liquid separation is 30 to 120 μm.
[0032] The invention provides a method for preparing an adsorbent for water treatment, comprising the following steps: a) ultrasonically treating and drying Artemia cyst shells that have been stirred and cleaned by a mixture of water and ethanol to obtain a clean material; b) calcining the obtained material at different pyrolysis temperatures to obtain Artemia cyst shells with different pore sizes; c) stirring the obtained Artemia cyst shells and prepared nano Fe3O4 particles and calcining them at high temperature to obtain an adsorbent for water treatment. The adsorbent for water treatment prepared by the invention can effectively remove copper ions from water. Different from the existing adsorbents, the invention prepares Artemia cyst shell iron oxide (LC-FeO) by cross-linking cheap Artemia cyst shells and nano Fe3O4. As a new type of adsorbent, LC-FeO has simple preparation conditions and can be prepared under conventional normal temperature and pressure conditions. Its internal pore structure allows nano Fe3O4 to grow in a confined area in the pores and change in size. It can not only quickly and efficiently adsorb copper ions in water, but also has strong magnetism, which is very conducive to recovery. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0034] Figure 1 This is a SEM image provided by Example 1 of the present invention.
[0035] Figure 2 This is the adsorption isotherm diagram provided in Example 2 of the present invention.
[0036] Figure 3 This is an adsorption kinetic diagram provided in Example 2 of the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The present invention provides a method for preparing an adsorbent for water treatment, comprising the following steps:
[0039] a) ultrasonically washing and drying the Artemia cysts that have been washed by stirring a mixture of water and ethanol to obtain a clean material;
[0040] b) firing the obtained materials at different pyrolysis temperatures to obtain Artemia cysts with different pore sizes;
[0041] c) stirring the obtained Artemia cysts and the prepared nano Fe3O4 particles and calcining them at a high temperature to obtain an adsorbent for water treatment.
[0042] In step a):
[0043] Ultrasonication and drying of the Artemia cysts washed by stirring a mixture of water and ethanol to obtain a clean material;
[0044] In certain embodiments of the present invention, the water and ethanol mass ratio is 1 to 3, specifically 1:1; the stirring time is 3 to 6 hours, specifically 5 hours;
[0045] The ultrasound time is 20 to 40 minutes, specifically 30 minutes;
[0046] The drying temperature is 50-80°C, specifically 60°C; the drying time is 6-9 hours, specifically 8 hours;
[0047] In step b):
[0048] The obtained materials are fired at different pyrolysis temperatures to obtain Artemia cysts with different pore sizes;
[0049] In certain embodiments of the present invention, the pyrolysis temperature is 0 to 900°C, specifically 60°C, 200°C, 500°C, 600°C, 700°C;
[0050] The firing time is 4 to 7 hours, specifically 5 hours
[0051] In step c):
[0052] The obtained Artemia cyst shells and the prepared nano Fe3O4 particles are stirred and fired at high temperature to obtain an adsorbent for water treatment.
[0053] In certain embodiments of the present invention, the nano Fe3O4 particles are prepared by stirring and mixing FeCl2·4H2O and FeCl3·6H2O in a mass ratio of 1 to 5, specifically, the mass ratio of FeCl2·4H2O to FeCl3·6H2O is 1:2;
[0054] Add 10-30 mL of aqueous ammonia (volume ratio is 10-40%), specifically add 20 mL of aqueous ammonia (volume ratio is 25%);
[0055] The heating at 60 to 90° C. for 10 to 40 minutes, specifically at 80° C. for 30 minutes, produces black nanoparticles;
[0056] The step of firing at 50 to 300° C. for 1 to 4 hours, specifically at 250° C. for 2 hours;
[0057] The mass ratio of Artemia cysts to nano-Fe3O4 is 1 to 5, and the stirring is performed for 1 to 3 hours, specifically, the mass ratio of Artemia cysts to nano-Fe3O4 is 1:1, and the stirring time is 2 hours;
[0058] The drying is performed at 60-100° C. for 8-16 hours, and the firing is performed at 200-700° C. for 1-4 hours, specifically, the drying is performed at 90° C. for 12 hours, and the firing is performed at 500° C. for 2 hours.
[0059] The present invention also provides an adsorbent for water treatment, including an adsorbent for water treatment prepared by the method for preparing the adsorbent for water treatment provided in the above embodiments.
[0060] The present invention also provides a water treatment method, comprising the following steps:
[0061] A) dissolving cupric sulfate pentahydrate into distilled water to obtain a copper ion solution;
[0062] B) adding a water treatment adsorbent to the copper ion solution to perform an adsorption reaction;
[0063] The adsorbent for water treatment is prepared by the method for preparing the adsorbent for water treatment;
[0064] C) performing solid-liquid separation on the water obtained in step B) to obtain treated water.
[0065] In step A):
[0066] Dissolve copper sulfate pentahydrate in distilled water to obtain a copper ion solution;
[0067] In certain embodiments of the present invention, before dissolving copper sulfate pentahydrate into distilled water, the method further comprises: using copper sulfate pentahydrate in an amount of 0.1 to 0.6 g, specifically 0.383 g / L;
[0068] The distilled water dosage is 50-200 mL, specifically 50 mL;
[0069] In step B):
[0070] adding an adsorbent for water treatment into a copper ion solution to perform an adsorption reaction;
[0071] The amount of the water treatment adsorbent is 0.01 to 1 g / L, specifically 0.2 g / L;
[0072] The water treatment adsorbent stays in the water body for 0.5 to 4 hours, specifically for 1 hour;
[0073] In step C):
[0074] The water body obtained in step B) is subjected to solid-liquid separation to obtain treated water body.
[0075] The pore size of the filter used for solid-liquid separation is 30-120 μm, specifically 50 μm.
[0076] The invention prepares magnetic iron oxide Artemia cysts by sintering Artemia cysts at a temperature other than pyrolysis and mixing Artemia cysts with nanoparticles, which not only greatly improves the adsorption performance of copper ions in water but also is very conducive to recovery.
[0077] In order to further illustrate the present invention, the preparation method and application of an adsorbent for water treatment provided by the present invention are described in detail below in combination with examples, but it should not be understood as limiting the scope of protection of the present invention.
[0078] Example 1
[0079] A water treatment adsorbent is prepared according to the following method:
[0080] 1. Add 5 g of Artemia cyst shells to 300 mL of a water-ethanol mixture (50% by mass) and stir for 5 hours to wash the raw cyst shells to remove salts and possible residues. Repeat the above procedure for 3-4 cycles. Afterwards, the Artemia cyst shells were ultrasonically treated for 30 minutes to achieve pore perforation and water penetration. The resulting material gradually tilted toward the bottom of the water, indicating that the water was fully saturated. Finally, the Artemia cyst shells were filtered and then heat treated at 60°C for 8 hours.
[0081] 2. Pyrolyze at 500°C for 5 hours and grind into powder.
[0082] 3. Dissolve FeCl2·4H2O and FeCl3·6H2O (mass ratio of 1:2) in 50ml of distilled water respectively and mix under vigorous stirring. Add 20mL of ammonia water (volume ratio of 25%) and stir continuously to precipitate the mixed solution. A black precipitate is formed immediately and heated at 80℃ for 30 minutes. The resulting black nanoparticles are removed by an external magnetic field, washed three times with double distilled water and ethanol, and then heated at 250℃ for 2 hours. The next step is to synthesize LC-FeO nanocomposites. Disperse Fe3O4 / Fe2O3 nanoparticles and Artemia cyst shells (mass ratio of 1:1) in double distilled water and stir continuously for 2 hours. The resulting nanoparticles are poured, filtered, washed several times with double distilled water, dried at 90℃ for 12 hours, and dried in a muffle furnace at 500℃ for 2 hours to obtain magnetic iron oxide Artemia cyst shells.
[0083] Electron microscope scanning was performed on Artemia cysts without iron loading and the magnetic Artemia cysts prepared in this example. The results are as follows: Figure 1 As shown, Figure 1 This is a SEM image provided by Example 1 of the present invention, wherein a, b, and c are Artemia cysts before loading with iron, and d, e, and f are Artemia cysts with magnetic iron oxide. Figure 1 It can be seen that a large number of small-sized nano-sized iron oxide particles are loaded in the pores of the magnetic iron oxide Artemia cyst shells prepared in this example, which proves that the method successfully loads nano-Fe3O4 onto Artemia cyst shells.
[0084] The magnetic iron oxide Artemia cyst shells prepared in this example were placed in a copper ion solution for adsorption, and their adsorption performance was tested. The results are as follows:
[0085] 1) The adsorption kinetics test results show that the magnetic iron oxide Artemia cyst shell material reaches saturation within 1 minute, and the adsorption rate is very fast.
[0086] 2) The adsorption isotherm test results show that the maximum copper ion adsorption capacity of the magnetic iron oxide Artemia cyst shell material is 219 mg / g.
[0087] 3) The regeneration performance test results show that after 5 adsorption-regeneration cycles, the adsorption capacity of the open-cell polymer foam material is still greater than 95%, and it has excellent regeneration performance.
[0088] 4) The adsorbent dispersed in water can be easily and completely recovered by applying an external magnetic field, which is very convenient.
[0089] Example 2
[0090] 1. Add 5 g of Artemia cyst shells to 300 mL of a water-ethanol mixture (50% by mass) and stir for 5 hours to wash the raw cyst shells to remove salts and possible residues. Repeat the above procedure for 3-4 cycles. Afterwards, the Artemia cyst shells were ultrasonically treated for 30 minutes to achieve pore perforation and water penetration. The resulting material gradually tilted toward the bottom of the water, indicating that the water was fully saturated. Finally, the Artemia cyst shells were filtered and then heat treated at 60°C for 8 hours.
[0091] 2. Pyrolyze at 600°C for 5 hours and grind into powder.
[0092] 3. Dissolve FeCl2·4H2O and FeCl3·6H2O (mass ratio of 1:2) in 50ml of distilled water respectively and mix under vigorous stirring. Add 20mL of ammonia water (volume ratio of 25%), stir continuously, and precipitate the mixed solution. A black precipitate is formed immediately, heated to 80℃ and kept for 30 minutes. The resulting black nanoparticles are removed by an external magnetic field, washed three times with double distilled water and ethanol, and then heated to 250℃ for 2 hours in an air atmosphere. The next step is to synthesize LC-FeO nanocomposites. Disperse Fe3O4 / Fe2O3 nanoparticles and Artemia cyst shells (1:1) in double distilled water and stir continuously for 2 hours. Pour the resulting nanoparticles, filter, wash several times with double distilled water, dry at 90℃ for 12 hours, and dry in a muffle furnace at 500℃ for 2 hours. Obtain magnetic iron oxide Artemia cyst shells.
[0093] The magnetic iron oxide Artemia cyst shells prepared in this example were placed in a copper ion solution for adsorption, and their adsorption performance was tested. The results are as follows:
[0094] 1) The adsorption kinetics test results show that the magnetic iron oxide Artemia cyst shell material reaches saturation within 1 minute, and the adsorption rate is very fast. Figure 2 This is an adsorption kinetic diagram provided in Example 2 of the present invention.
[0095] 2) The adsorption isotherm test results show that the maximum copper ion adsorption capacity of the magnetic iron oxide Artemia cyst shell material is 191 mg / g. Figure 3 It is an adsorption isotherm diagram provided by Embodiment 2 of the present invention.
[0096] 3) The regeneration performance test results show that after 5 adsorption-regeneration cycles, the adsorption capacity of the open-cell polymer foam material is still greater than 95%, and it has excellent regeneration performance.
[0097] 4) The adsorbent dispersed in water can be easily and completely recovered by applying an external magnetic field, which is very convenient.
[0098] Example 3
[0099] 1. Add 5 g of Artemia cyst shells to 300 mL of a water-ethanol mixture (50% by mass) and stir for 5 hours to wash the raw cyst shells to remove salts and possible residues. Repeat the above procedure for 3-4 cycles. Afterwards, the Artemia cyst shells were ultrasonically treated for 30 minutes to achieve pore perforation and water penetration. The resulting material gradually tilted toward the bottom of the water, indicating that the water was fully saturated. Finally, the Artemia cyst shells were filtered and then heat treated at 60°C for 8 hours.
[0100] 2. Pyrolyze at 700°C for 5 hours and grind into powder.
[0101] 3. Dissolve FeCl2·4H2O and FeCl3·6H2O (mass ratio of 1:2) in 50ml of distilled water respectively and mix under vigorous stirring. Add 20mL of ammonia water (volume ratio of 25%) and stir continuously to precipitate the mixed solution. A black precipitate is formed immediately and heated to 80℃ for 30 minutes. The resulting black nanoparticles are removed by an external magnetic field, washed three times with double distilled water and ethanol, and then heated at 250℃ for 2 hours. The next step is to synthesize LC-FeO nanocomposites. Disperse Fe3O4 / Fe2O3 nanoparticles and Artemia cyst shells (mass ratio of 1:1) in double distilled water and stir continuously for 2 hours. Pour the resulting nanoparticles, filter, wash several times with double distilled water, dry at 90℃ for 12 hours, and dry in a muffle furnace at 500℃ for 2 hours to obtain magnetic iron oxide Artemia cyst shells.
[0102] The magnetic iron oxide Artemia cyst shells prepared in this example were placed in a copper ion solution for adsorption, and their adsorption performance was tested. The results are as follows:
[0103] 1) The adsorption kinetics test results show that the magnetic iron oxide Artemia cyst shell material reaches saturation within 1 minute, and the adsorption rate is very fast.
[0104] 2) The adsorption isotherm test results show that the maximum copper ion adsorption capacity of the magnetic iron oxide Artemia cyst shell material is 171 mg / g.
[0105] 3) The regeneration performance test results show that after 5 adsorption-regeneration cycles, the adsorption capacity of the open-cell polymer foam material is still greater than 95%, and it has excellent regeneration performance.
[0106] 4) The adsorbent dispersed in water can be easily and completely recovered by applying an external magnetic field, which is very convenient.
[0107] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an adsorbent for water treatment, characterized in that: The following steps are involved: a) ultrasonically washing the Artemia cysts that have been washed by stirring a mixture of water and ethanol and drying the mixture to obtain a clean material; b) firing the obtained materials at different pyrolysis temperatures to obtain Artemia cysts with different pore sizes; c) stirring the obtained Artemia cysts and the prepared nano Fe3O4 particles and calcining them at a high temperature to obtain an adsorbent for water treatment.
2. The method for preparing the adsorbent for water treatment according to claim 1, characterized in that: In step a), the ethanol and water are mixed in a mass ratio of 1 to 3 and stirred for 3 to 6 hours; Ultrasound time is 20 to 40 minutes; The drying temperature is 50-80°C and the time is 6-9 hours.
3. The method for preparing the adsorbent for water treatment according to claim 1, characterized in that: Step b), the pyrolysis temperature is 0 to 900°C; The firing time is 4 to 7 hours.
4. The method for preparing the adsorbent for water treatment according to claim 1, characterized in that: Step c), the nano Fe3O4 particles are prepared by stirring and mixing FeCl2·4H2O and FeCl3·6H2O in a mass ratio of 1 to 5; Add 10-30 mL of aqueous ammonia (volume ratio is 10-40%) and heat at 60-90° C. for 10-40 minutes; Firing at 50-300°C for 1-4 hours; The mass ratio of Artemia cyst shell to nano-Fe3O4 is 1 to 5, and the mixture is stirred for 1 to 3 hours; Dry at 60-100°C for 8-16 hours and sinter at 200-700°C for 1-4 hours.
5. An adsorbent for water treatment, characterized in that: The invention comprises an adsorbent for water treatment prepared by the method for preparing an adsorbent for water treatment as claimed in any one of claims 1 to 4.
6. A water treatment method, characterized in that: The following steps are involved: A) dissolving cupric sulfate pentahydrate into distilled water to obtain a copper ion solution; B) adding a water treatment adsorbent to the copper ion solution to perform an adsorption reaction; The water treatment adsorbent is the water treatment adsorbent according to claim 5; C) performing solid-liquid separation on the water obtained in step B) to obtain treated water.
7. The water treatment method according to claim 6, characterized in that: In step A), before dissolving copper sulfate pentahydrate into distilled water, the method further comprises: using 0.1 to 0.6 g of copper sulfate pentahydrate; The amount of distilled water used is 50-200 mL; In step B), the amount of adsorbent for water treatment is 0.01 to 1 g / L; The water treatment adsorbent stays in the water body for 0.5 to 4 hours; The adsorption reaction is carried out at room temperature; In step C), the pore size of the filter used for solid-liquid separation is 30 to 120 μm.